Protective Effects of Aju Mbaise Extract against Dutasteride-Induced Biochemical and Haematological Changes in Rats - Robert Ikechukwu Uroko; Paul Chukwuemaka Nweje-Anyalowu; Ikenna Obiwuru; Ogwo Elisha Uko; Chinomso Friday Aaron; Obinna Joseph Mba (Herbal Medicines Journal, 2022)
Background and Aim: Aju Mbaise is a nutraceutical food supplement taken by nursing mothers within their first three months of delivery due to its health advantages. This study evaluated the protective potentials of Aju Mbaise extract on the renal functions, lipid profile, and haematological indices of Dutasteride-induced rats.